Directed evolution of excited state lifetime and brightness in FusionRed using a microfluidic sorter. Issue 9 (10th August 2018) - Manna, Premashis; Hung, Sheng-Ting; Mukherjee, Srijit; Friis, Pia; Simpson, David M.; Lo, Maria N.; Palmer, Amy E.; Jimenez, Ralph
Abstract : Directed evolution of fluorescent proteins with lifetime and brightness selections leads to improved variants. Abstract : Green fluorescent proteins (GFP) and their blue, cyan and red counterparts offer unprecedented advantages as biological markers owing to their genetic encodability and straightforward expression in different organisms. Although significant advancements have been made towards engineering the key photo-physical properties of red fluorescent proteins (RFPs), they continue to perform sub-optimally relative to GFP variants. Advanced engineering strategies are needed for further evolution of RFPs in the pursuit of improving their photo-physics. In this report, a microfluidic sorter that discriminates members of a cell-based library based on their excited state lifetime and fluorescence intensity is used for the directed evolution of the photo-physical properties of FusionRed. In-flow measurements of the fluorescence lifetime are performed in a frequency-domain approach with sub-millisecond sampling times. Promising clones are sorted by optical force trapping with an infrared laser. Using this microfluidic sorter, mutants are generated with longer lifetimes than their precursor, FusionRed. This improvement in the excited state lifetime of the mutants leads to an increase in their fluorescence quantum yield up to 1.8-fold. In the course of evolution, we also identified one key mutation (L177M), which generated a mutant (FusionRed-M) that displayed ∼2-fold higher brightness than its precursor upon expression in mammalian (HeLa) cells. Photo-physical and mutational analyses of clones isolated at the different stages of mutagenesis reveal the photo-physical evolution towards higher in vivo brightness.